The Relationship of Self-Concept with and Family Support Student's Learning Motivation in Online Learning - Rasyida, Nuril Arga; Hakim, Siti Nurina (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Use of online media is one solution so that teaching and learning activities between teachers and students can continue to be carried out, although in its implementation online media are not uncommon problems. The decision to switch to online learning media will affect the conducive interaction between teachers and students, if the method used is not suitable it will make students less interested and bored, the impact is that students become lazy, passive, and less interested in learning. The purpose of this study was to determine the relationship between self-concept and family support on students' learning motivation. The research hypotheses are: (1) there is a relationship between self-concept and family support with learning motivation, (2) there is a positive relationship between self-concept and learning motivation, (3) there is a positive relationship between family support and learning motivation. This research uses correlational quantitative methods. The research population was students of SMP 1 Muhammadiyah Surakarta. A sample of 100 students was determined by purposive sampling. The data collection tool uses the Learning Motivation Scale, the Self-Concept Scale, and the Family Support Scale. The data analysis technique used multiple linear regression. The results of multiple regression analysis get the results (F) = 134.999 with a sig.p < 0.01, value (r) = 0.847 (r > 0), with a value of Sig. (1-tailed) p < 0.01, and the value (r) = 0.652 (r > 0), with a value of Sig. (1-tailed) p <0.01.indicates that there is a very significant positive relationship between self-concept and family support with learning motivation, shows a very significant positive relationship between self-concept and learning motivation, and shows a very significant positive relationship between family support and learning motivation.